2011
DOI: 10.1007/s00244-011-9652-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exposure to Glyphosate Herbicide Affects Oxidative Parameters in Piava (Leporinus obtusidens)

Abstract: In recent years, commercial glyphosate herbicide formulations have been widely used in agriculture to control aquatic weeds. These pesticides may result in disruption of ecological balance, causing damage to nontarget organisms including fish. Teleostean fish (Leporinus obtusidens) were exposed to commercial glyphosate herbicide formulation at 0 (control), 3, 6, 10 or 20 mg L(-1) for 96 h. The effects of herbicide on plasmatic metabolic parameters, thiobarbituric acid reactive substances (TBARS), catalase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 34 publications
5
47
0
3
Order By: Relevance
“…AChE activity was measured as described by [16] and modified [17]. Lipid peroxidation was estimated by a thiobarbituric acid reactive substance (TBARS) assay [18]. The second portion of the homogenates was added to 8.1% sodium dodecyl sulfate (SDS) and 2.5M acetic acid (pH 3.34).…”
Section: Experimental Designmentioning
confidence: 99%
“…AChE activity was measured as described by [16] and modified [17]. Lipid peroxidation was estimated by a thiobarbituric acid reactive substance (TBARS) assay [18]. The second portion of the homogenates was added to 8.1% sodium dodecyl sulfate (SDS) and 2.5M acetic acid (pH 3.34).…”
Section: Experimental Designmentioning
confidence: 99%
“…A similar study was reported on Oreochromis niloticus by Ayoola (2008). Oxidative parameters were reported by Glusczak et al (2011) to be impacted in Piava (Leporinus obtusidens) on exposure to acute concentrations of glyphosate. Genotoxicity and cytotoxicity arising from glyphosate exposure have also been reported in the blood of fish by some other researchers (Cavalcante et al, 2008;Moreno et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, some investigators have shown that aquatic organisms, particularly fish, could be more sensitive to glyphosate compared with mammals (Lushchak et al 2009). Roundup formulation affected energy metabolism, hematological parameters, histological morphology, freeradical processes, and acetylcholinesterase activity in several fish species (Langiano & Martinez 2008;Lushchak et al 2009;Glusczak et al 2006Glusczak et al , 2007Glusczak et al , 2011Menezes et al 2011).…”
mentioning
confidence: 99%